Zlecenia stop-loss z perspektywy finansów behawioralnych - Kicia, Mariusz (Stop-loss Orders - a Behavioural Finance Perspective, 2007)
Behavioural Finance discoveries show that decisions investors make during the stock market investment depend on previous gains or losses. The author presents that disposition effect (riding losers too long and selling winners too early) is a common mistake investors make. Although institutional investors do not avoid such non-effectiveness slice finally it takes a human to make a decision, some loses can be avoided by the limiting. One of the common rules uses stop-loss orders to cut the losses automatically. The article analyzes how stop-loss orders can be helpful in portfolio management process but also can limit some behavioural disposition effect.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 286-294